Spheroid trilineage differentiation model of primary mesenchymal stem/stromal cells under hypoxia and serum-free culture conditions - Moldaschl, Julia; Chariyev-Prinz, Farhad; Toegel, Stefan; Keck, Maike; Hiden, Ursula; Egger, Dominik; Kasper, Cornelia (Frontiers in Bioengineering and Biotechnology, 2024)
Due to their unique properties, human mesenchymal stem/stromal cells (MSCs) possess tremendous potential in regenerative medicine, particularly in cell-based therapies where the multipotency and immunomodulatory characteristics of MSCs can be leveraged to address a variety of disease states. Although MSC-based cell therapeutics have emerged as one of the most promising medical treatments, the clinical translation is hampered by the variability of MSC-based cellular products caused by tissue source-specific differences and the lack of physiological cell culture approaches that closely mimic the human cellular microenvironment. In this study, a model for trilineage differentiation of primary adipose-, bone marrow- and umbilical cord-derived MSCs into adipocytes, chondrocytes and osteoblasts was established and characterized. Differentiation was performed in spheroids culture, using hypoxic conditions and serum-free and antibiotics-free medium. This platform was characterized for spheroid diameter and trilineage differentiation capacity reflecting functionality of differentiated cells, as indicated by lineage-specific extracellular matrix (ECM) accumulation and expression of distinct secreted markers. The presented model shows spheroid growth during the course of differentiation and successfully supports trilineage differentiation for MSCs from almost all tissue sources except for osteogenesis of umbilical cord-derived MSCs. These findings indicate that this platform provides a suitable and favorable environment for trilineage differentiation of MSCs from various tissue sources. Therefore, it poses a promising model to generate highly relevant biological data urgently required for clinical translation and therefore might be used in the future to generate in vitro microtissues, building blocks for tissue engineering or as disease models.